Chiral Discrimination through 1H NMR and Luminescence Spectroscopy: Dynamic Processes and Solid Strip for Chiral Recognition. Issue 72 (14th December 2017) - Gangopadhyay, Monalisa; Maity, Arunava; Dey, Ananta; Rajamohanan, P. R.; Ravindranathan, Sapna; Das, Amitava
Abstract: The appropriate choice of the host molecules with well‐defined optical activity ( S ‐H/ R ‐H) helps in the differentiation between two secondary ammonium ion‐derivative guest molecules with different optical activities ( R ‐G/ S ‐G) based on the fluorescence resonance energy transfer (FRET)‐based luminescence responses. Crown ether‐based host molecules with opposite chiral configurations ( R ‐H, S ‐H) have been derived from 1, 1′‐bi‐2‐naphthol (BINOL) derivatives that have axially chiral biaryl centers. These chiral crown ethers form host–guest complexes (i.e., [2]pseudorotaxanes) with chiral secondary ammonium ion derivatives ( R ‐G, S ‐G). NMR spectroscopic studies show that the complexes are in a dynamic equilibrium in solution. Results of the 1 H NMR and fluorescence spectroscopic studies indicate a head‐on orientation of the host and guest in the [2]pseudorotaxanes. The difference in the efficiency in the FRET‐based responses between anthracene and the BINOL derivatives allow efficient chiral discrimination of the guests. Isothermal titration calorimetry and NMR investigations reveal that inclusion complexes between hosts and guests of the same chirality ( R ‐H⋅ R ‐G, S ‐H⋅ S ‐G) are more stable relative to those of opposite chirality ( R ‐H⋅ S ‐G, S ‐H⋅ R ‐G). However, FRET‐based energy‐transfer efficiency is higher for R ‐H⋅ S ‐G and S ‐H⋅ R ‐G complexes. NMR spectroscopic studies show that the relative orientation of the guest in the host cavity is significantly different when the host binds a guest of the same or opposite chirality; furthermore, the latter is more favorable for FRET, thus enabling discrimination between enantiomers. Interestingly, chiral discrimination of guest ions could also be achieved by using silica surfaces modified with chiral host molecules. Abstract : Positive discrimination : Crown ether‐based host molecules with well‐defined optical activities ( S ‐H/ R ‐H) help to differentiate between guest molecules with different optical activities ( R ‐G/ S ‐G) based on fluorescence resonance energy transfer (FRET)‐based luminescence responses. The physicochemical and thermodynamic parameters for the host–guest adduct are influenced by the relative orientation of the optically pure guest inside the cavity of the enantiomerically pure host during the self‐assembly process.